Concretes on a composite gypsum binder using limestone stone crushing waste - Natalia V Chernysheva; Othman Azmi SA; Motorykin Dmitry Aleksandrovich (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
The article discusses the possibility of obtaining Composite Gypsum Binders (CGB) and heavy concretes based on them using local raw materials from Palestine. As an active mineral additive in the composition of the composite gypsum binder, it is proposed to use finely dispersed quartz sand with a specific surface area of ​​500 m2/kg, on the surface of which, during grinding, a disturbed microlayer is formed containing a limited amount of amorphous SiO2, which is capable of binding Ca(OH)2 at ordinary temperatures with the formation of insoluble compounds, that is, it has pozzolanic activity, and as a result provides a significant increase in the strength of composites, increases their water resistance. Based on the developed composite gypsum binder with sufficiently high strength (24.8 MPa) and water resistance (K = 0.73), heavy concretes were obtained with a class of compressive strength B7.5 - B15, for use in residential, public, and industrial buildings in the form of load-bearing, self-supporting and enclosing structures.